Image and feature reconstruction for the attenuated Radon transform via circular harmonic decomposition of the kernel. (30th January 2015) - Rigaud, G; Lakhal, A
Abstract: This paper is concerned with a method of image reconstruction and feature extraction for the attenuated Radon transform in two dimensions based on the decomposition in circular harmonics of the integral kernel in Novikovʼs inversion formula for an arbitrary known attenuation. This analytical decomposition of the reconstruction kernel provides an alternative reconstruction algorithm. Besides, we propose to use our formula to directly extract features of the object with no need for process imaging techniques. Numerical results attest to the strengths and limitations of our reconstruction method in terms of accuracy and robustness for image and feature reconstruction.